A Case Report of Schwannoma Presenting as Sciatica - A Afshar Fard; M Hassani; H MolaeiGhovarchinGhalee; F Hoseinzadegan; H Zohouri; S Naserinia (Armaghane Danesh Bimonthly Journal, 2012)
Background & aim: Schwannomas are benign and slowly growing nerve sheath tumors which are usually solitary and encapsulated. They may arise from any peripheral nerve containing Schwann cells including distal portions of cranial nerves. Here we are reporting a case of Schwannoma presenting as sciatica.